2009
DOI: 10.1007/s10584-009-9640-0
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal temperatures over Italy and their relationship with low-frequency atmospheric circulation patterns

Abstract: An analysis of Italian seasonal temperatures from 1961 to 2006 was carried out, using homogenized data from 49 synoptic stations well distributed throughout Italy. The results show remarkable differences among seasons. Stationarity characterizes winter series, except for Northern Italy (where a warming trend from 1961 is identified); a positive trend over the entire period is recognized for spring series. Summer series are marked by a negative trend until 1981 and by a positive trend afterwards; finally, autum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 37 publications
(36 reference statements)
10
50
0
Order By: Relevance
“…A few recent papers have demonstrated a strong influence of the EA on the air− sea heat exchange and temperature over the Medi terranean regions (deCastro et al 2008, Schroeder et al 2010, Josey et al 2011), whereas Toreti et al (2010) found a strong relationship between air temperatures and the EA all over Italy. The impact of the EMP on precipitation extremes over Cyprus has been studied by Hatzaki et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…A few recent papers have demonstrated a strong influence of the EA on the air− sea heat exchange and temperature over the Medi terranean regions (deCastro et al 2008, Schroeder et al 2010, Josey et al 2011), whereas Toreti et al (2010) found a strong relationship between air temperatures and the EA all over Italy. The impact of the EMP on precipitation extremes over Cyprus has been studied by Hatzaki et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have carried out temperature trend analysis at different spatial scales, for instance: Schönwiese and Rapp (1997), Parry (2000), Klein Tank et al (2002), Klein Tank and Können (2003), Klein Tank et al (2005), Luterbacher et al (2004), and Moberg et al (2006) for all Europe or Brunetti et al (2000Brunetti et al ( , 2004Brunetti et al ( , 2006, Toreti and Desiato (2008), and Toreti et al (2010) in Italy; Degirmendžić et al (2004) in Poland; Rebetez and Reinhard (2008) in Switzerland; Wulfmeyer and Henning-Müller (2006) in Germany; Chaouche et al (2010) in France;and Feidas et al (2004) in Greece. Although there are local and regional differences most of Europe has experienced rising temperatures of about 0.8°C during the 20th century (IPCC, 2001) showing similar patterns to the global or a hemispheric scale.…”
Section: Introductionmentioning
confidence: 99%
“…1. We have analyzed only mean summer temperatures (even though temperature data are available at each month and season of the year) because large-scale climate changes appear to be most articulated during the summer months (e.g., (Toreti et al 2010;Croitoru et al 2011)). …”
Section: Datamentioning
confidence: 99%
“…The model discussed in Lund and Reeves (Lund and Reeves 2002) and Toreti et al (Toreti et al 2010) proposes to obtain an estimated value for the change point c by maximizing an F statistic. To determine if the change is statistically significant (i.e., a true change point), Lund and Reeves (Lund and Reeves 2002) compared the observed max F statistic with critical values obtained by simulation under a null hypothesis of "no change" at c (see (Lund and Reeves 2002) for more details).…”
Section: Datamentioning
confidence: 99%